Comparative study of g-C₃N₄/Cu₂O and BiVO₄/Cu₂O photocathodes for enhanced electricity generation and hydrogen evolution in photocatalytic fuel cells - Muhammad Fahmi Hakim; Muhammad Febriansyah Bachri; Ratnawati Ratnawati; Rike Yudianti; Muhammad Ibadurrohman; Slamet Slamet (International Journal of Renewable Energy Development, 2026)
The preparation of good photocathodes is a crucial issue regarding promoting the performance of photocatalytic fuel cell (PFC) systems for environmentally protective energy conversion approaches. In the present work, a comparative study of Cu₂O-based photocathodes jointly modified with graphitic carbon nitride (g-C₃N₄) and bismuth vanadate (BiVO₄) was performed to ascertain their competence towards concomitant electricity generation and hydrogen evolution in an integrated single-chamber photocatalytic fuel cell. Cu substrates were anodized to produce ordered Cu₂O layers, modified with immersion treatments, and then low-temperature calcination. The as-prepared products were characterized in detail by XRD, HR-TEM, UV–Vis DRS, PL spectra, and XPS analyses, as well as photoelectrochemical measurements to gain insight into crystallinity, morphology, photocatalytic activity (optical absorption), electronic structure, and charge recombination. Results revealed that among the pristine Cu₂O and g-C₃N₄/Cu₂O, superior charge separation was exhibited on the BiVO₄/Cu₂O photocathode, along with better power density and hydrogen evolution. The highest power density of BiVO₄/Cu₂O was 0.05625 mW cm⁻² and 13.71 mmol.m⁻² for hydrogen evolution compared to both Cu₂O (0.0375 mW cm⁻²;11.19 mmol.m⁻²) and g-C₃N₄/Cu₂O (0.026 mW cm⁻²; 8.1616 mmol m-2). This observation was supported by the analysis of the photoluminescence spectra: BiVO₄/Cu₂O had PL intensity of 325 a.u., lower than Cu₂O (400 a.u.) and g-C₃N₄/Cu₂O (650 a.u.), validating that this sample more effectively suppressed electron–hole recombination and electron transport mechanism. The enhanced photocatalytic activity of BiVO₄/Cu₂O is associated with the generation of a p-n heterojunction, which accumulates a built-in electric field to drive effective charge separation and offers visible-light sensitization upon its larger absorption spectrum that is beneficial for not only promoting hydrogen evolution efficiency but also improving electricity production in PFC systems.